Cortical β-amyloid burden, neuropsychiatric symptoms, and cognitive status: the Mayo Clinic Study of Aging - Krell-Roesch, Janina; Vassilaki, Maria; Mielke, Michelle M; Kremers, Walter K; Lowe, Val J; Vemuri, Prashanthi; Machulda, Mary M; Christianson, Teresa J; Syrjanen, Jeremy A; Stokin, Gorazd B; Butler, Lesley M; Traber, Martin; et al. (Translational psychiatry, 2019)
Neuropsychiatric symptoms (NPS) are a risk factor for cognitive impairment and are associated with cortical β-amyloid (Aβ) deposition. We conducted a cross-sectional study derived from the ongoing population-based Mayo Clinic Study of Aging to examine the frequency of NPS among cognitively unimpaired (CU) and mild cognitive impairment (MCI) participants who either have normal (A-) or abnormal (A+) Aβ deposition. We also investigated whether combined presence of MCI and amyloid positivity (MCI/A+) is associated with greater odds of having NPS as compared to CU/A- (defined as reference group). Participants were 1627 CU and MCI individuals aged ≥ 50 years (54% males; median age 73 years). All participants underwent NPS assessment (Neuropsychiatric Inventory Questionnaire (NPI-Q); Beck Depression Inventory II (BDI-II); Beck Anxiety Inventory (BAI)) and 11C-PiB-PET. Participants with an SUVR > 1.42 were classified as A+. We conducted multivariable logistic regression analyses adjusted for age, sex, education, and APOE ε4 genotype status. The sample included 997 CU/A-, 446 CU/A+, 78 MCI/A-, and 106 MCI/A+ persons. For most NPS, the highest frequency of NPS was found in MCI/A+ and the lowest in CU/A-. The odds ratios of having NPS, depression (BDI ≥ 13), or anxiety (BAI ≥ 8, ≥ 10) were consistently highest for MCI/A+ participants. In conclusion, MCI with Aβ burden of the brain is associated with an increased risk of having NPS as compared to MCI without Aβ burden. This implies that the underlying Alzheimer's disease biology (i.e., cerebral Aβ amyloidosis) may drive both cognitive and psychiatric symptoms.
Keywords: Amyloid beta-Peptides; Cross-Sectional Studies; Neuropsychological Tests; senioři nad 80 let; mozek; pozitronová emisní tomografie; Humans; Brain; neuropsychologické testy; lidé středního věku; Cognitive Dysfunction; Aged, 80 and over; logistické modely; Middle Aged; Positron-Emission Tomography; Logistic Models; Alzheimerova nemoc; mužské pohlaví; úzkost; Alzheimer Disease; Aging; Depression; průřezové studie; kognitivní dysfunkce; Anxiety; ženské pohlaví; amyloidní beta-protein; lidé; deprese; Aged; senioři; Male; stárnutí; Female